Faktor Yang Berhubungan Dengan Tindakan Tidak Aman Pekerja Bagian Produksi PDAM Ratulangi Kota Makassar (Window of Public Health Journal, 2025)
Data from the International Labor Organization (ILO) shows that every day, there are around 6,000 fatal work accidents in the world, and more than 160 million workers become ill due to hazards/unsafe actions in the workplace. This is influenced by unsuitable tools and safety equipment that do not meet standards. Unsafe actions are actions that can endanger the workers themselves, such as operating machinery without proper training, not using personal protective equipment, or working in unsafe conditions. This study aims to determine the factors related to these unsafe actions in production workers at PDAM Ratulangi, Makassar City, in 2023. The type of research is quantitative research using the cross-sectional study method. The study population was all production workers at PDAM Ratulangi, Makassar City, with as many as 43 people and a sample of 43 people using the total Sampling method. Data was taken using a questionnaire and then analyzed using the chi-square test. From the research results, it was obtained that there was a relationship between supervision and unsafe actions in production workers at PDAM Ratulangi, Makassar City, in 2023, namely (p = 0.000